Healthy Living: Hyperglycemia and Hypoglycemia - Jennifer Hillan (EDIS)
FCS8820, a 2-page fact sheet by Jennifer Hillan, helps patients with diabetes understand how to detect, treat, and prevent hyperglycemia (high blood sugar) and hypoglycemia (low blood sugar). Published by the UF Department of Family, Youth and Community Sciences, December 2006.